2016
DOI: 10.1021/acsami.6b13097
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Semi-IPN Hydrogel Microfibers from Continuous Fluidic Processing with High Elasticity and Fast Actuation

Abstract: Hydrogels with rapid and strong response to external stimuli and possessing high elasticity and strength have been considered as platform materials for numerous applications, e.g., in biomaterials engineering. Thermoresponsive hydrogels based on semi-interpenetrating polymer networks (semi-IPN) featuring N-isopropylacrylamide with copolymers of poly(N-isopropylacrylamide-co-hydroxyethyl methacrylate) p(NIPAM-HEMA) chains are prepared and described. The copolymer was characterized by FTIR, NMR, and GPC. The sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 61 publications
3
101
0
Order By: Relevance
“…The spectrum of the nanogels exhibited main peaks at 1645 and 1540 cm −1 , which represented the chemical bond for amide I and amide II of NIPAM, respectively . The band around 1713 cm −1 was assigned to the carbonyl group of HEMA, which indicated that the poly(NIPAM‐HEMA) nanogels successfully formed (Figure S1, Supporting Information). The modulus‐cyclable hydrogel was fabricated by introducing the thermoreversible nanogel into the GelMA to form interpenetrating networks throughout UV irradiation (10 mW cm −2 , 365 nm, 80 s) in the presence of lithium acylphosphinate (LAP) as a photoinitiator, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of the nanogels exhibited main peaks at 1645 and 1540 cm −1 , which represented the chemical bond for amide I and amide II of NIPAM, respectively . The band around 1713 cm −1 was assigned to the carbonyl group of HEMA, which indicated that the poly(NIPAM‐HEMA) nanogels successfully formed (Figure S1, Supporting Information). The modulus‐cyclable hydrogel was fabricated by introducing the thermoreversible nanogel into the GelMA to form interpenetrating networks throughout UV irradiation (10 mW cm −2 , 365 nm, 80 s) in the presence of lithium acylphosphinate (LAP) as a photoinitiator, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The preparation scheme of the P(NIPAM‐ co ‐DMC)/Na 2 WO 4 hydrogel was depicted in Scheme . During the copolymerization of NIPAM and DMC in the presence of Na 2 WO 4 , WO 4 – is more inclined to interact with ammonium groups of DMC by salt bonding according to HSAB principle. As a result, the resultant NaCl was washed out to leave the hydrogel with porous structure after the washing.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al . synthesized a core–shell microfiber system with a sodium alginate core and semi interpenetrating polymer network shell consisting of PNIPAAm copolymerized with poly( n ‐isopropylacrylamide‐ co ‐hydroxyethylmethacrylate), as shown in Figure . The elasticity of these microfibers was examined by attaching a load of 3.6 g at one end and raising the environmental temperature to above LCST, where the microfiber collapsed in length, and subsequently lowering the temperature, finding the microfiber returning to its original length.…”
Section: Synthetic Smart Polymersmentioning
confidence: 99%